Changes in perceptions of urban green space are related to changes in psychological well-being: Cross-sectional and longitudinal study of mid-aged urban residents. (September 2019) - Cleary, Anne; Roiko, Anne; Burton, Nicola W.; Fielding, Kelly S.; Murray, Zoe; Turrell, Gavin
Abstract: We used data from 5, 014 mid-aged adults in the HABITAT study, across two waves (2009 and 2011), to explore associations between perceptions of quantity of urban green space and psychological well-being. Linear regression revealed that perceptions of urban green space quantity were significantly and positively associated with psychological well-being at both time-points. A longitudinal, fixed effects, two-period difference regression revealed that within-person change in perceptions of green space quantity across two years was positively associated with psychological well-being. All associations remained significant after controlling for age, gender, household income, education, occupation and neighbourhood disadvantage. Our findings indicate that psychological well-being is associated with perceptions of local urban green space. Subjective measures of green space are an important factor that need to be considered when exploring the relationship between green space and mental health. These findings are timely given the growing interest in urban green space interventions for combating increasing mental ill-health rates as well as promoting well-being among expanding urban populations. Highlights: We assessed how changes in perceptions of green space relate to changes in well-being. This is the first time this relationship has been investigated within a longitudinal study. Perceiving greater quantity of green space is associated with improved well-being. Subjective measures of green space should be included in future studies.